Proceedings of National Seminar on Regulations and Governance Issues in India’s Seed Sector - Dadlani, Narendra (International Food Policy Research Institute, 2025)
India has a very mature and vibrant seed sector with a wide network of public and private sector enterprises working closely together to make quality seeds available to farmers at affordable prices, ensuring seed security in the country. Presently ranked fifth in the global seed trade with a reported turnover of more than USD 6 billion India is likely to double this figure by 2028 due to a healthy growth rate (CAGR) which is already faster than the global rate. With improved seed replacement rate (SRR) of major food security crops, better variety replacement rate (VRR) in most crops and a declining informal trade of farm saved seed (FSS), the industry is showing a strong upswing in its growth. Much of this progress can be attributed to the continued scientific contributions of both the public and private sector which were assisted by the enabling policies of the government. A National Seminar on ‘Regulations and Governance Issues in Indian Seed Sector’ was organized on 26-27 September 2023 at New Delhi by the International Food Policy Research Institute (IFPRI), South Asia Regional Office, New Delhi, in collaboration with CGIAR Initiative on Seed Equal, Indian Council of Agricultural Research (ICAR), New Delhi and the Federation of Seed Industry of India (FSII), New Delhi. The Seminar was Inaugurated by Dr. Himanshu Pathak, Secretary, Department of Agricultural Research & Education (DARE) and Director General, ICAR. Dr. P.K. Singh, Agriculture Commissioner, Ministry of Agriculture & Farmers’ Welfare, Govt. of India, presided over the Inaugural Session, which was also addressed by Dr. M. Ramasami, Chairman, FSII. A total of 122 scientists, industry professionals, policy makers and other stakeholders, participated in the seminar.